Analisis Potensi Ekowisata, Agrowisata Dan Wisata Kuliner Untuk Pariwisata Berkelanjutan Di Desa Cibitung Wetan, Kabupaten Bogor - Teddy Chandra; Sukarno Wibowo; Dhonny Yusuf Amier (Penerbit Lafadz Jaya, 2026)
This study aims to analyze various potentials of ecotourism, agrotourism, and culinary tourism for the development of sustainable tourism in Cibitung Wetan Village, Pamijahan District, Bogor Regency. This study was conducted to answer the following research questions: 1) How is the description of ecotourism in Cibitung Wetan Village, Bogor Regency; 2) How is the description of agrotourism in Cibitung Wetan Village, Bogor Regency; and 3) How is the description of culinary tourism in Cibitung Wetan Village, Bogor Regency. This study was conducted using qualitative research methods. Data collection techniques were carried out through: observation, literature study, and interviews. The results of the study indicate that Cibitung Wetan is one of the villages located around the foothills of the Halimun-Salak National Park mountains with various potential tourist attractions that are very worthy of being developed to support the development of sustainable tourism such as the potential for ecotourism, agrotourism, and also culinary tourism. The potential ecotourism in Cibitung Wetan village includes Curug Lontar, Curug Batu Nawing, River Tubing Cianten, and the Lebak Karang camping ground. Potential agrotourism destinations in Cibitung Wetan Village include the Cakadut durian agrotourism and the upland rice educational agrotourism area. Furthermore, Cibitung Wetan Village also boasts culinary tourism opportunities, such as durian dodol (dodol durian), durian wajik (durian wajik), and durian pancakes.